Efektifitas Sertifikasi Nadzir Dalam Sektor Pengelolaan Wakaf Di Indonesia - Muslihati, Muslihati; Ruqayyah Yunus, Ayu; Anwar, Nurfiah (MADINAH, 2022)
As for the topic of the problem in this study, how is the validity of nadzir certification in the Indonesian waqf management department and the validity of the nadzir's role in the Indonesian waqf management department on the subject of this research? Furthermore, the purpose of this study is to determine the effectiveness of nadzir certification in the Indonesian waqf management department and the effectiveness of the nadzir's role in the waqf management department in Indonesia. The search method used is a literature search. The references in this article are based on the ideas and results of previous research such as journals, books and articles. The results of this study indicate that Wakaf Nadzir will issue certificates to move from individual Nadzir to institutional or legal Nadzir, ensuring management security and property security, safeguarding the unity and future of the ummah. It also shows that it helps to avoid potential conflicts. With human skills, technical people and quality relationships, professional Nazir is a general leader in Waqf institutions who are able to achieve Waqf goals.